The causes of pure conductive hearing loss in relation with age groups - Hamood, Manal A.; Alsarhan, Haider W.; Dawood, Mohammed R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Pure conductive hearing loss might be detected at any age, that made verbal communication is a problem issue, as well as, educational and social implications, therefore, earlier diagnosis and treatment of this problem is essential, since it`s have impact on patient`s life quality. To assess the causes of pure conductive hearing loss in relation with the age group. Methods: A prospective observational study, where 38 patients at Otolaryngology unit were selected after taking a precise history, full (Ear, Nose and Throat) clinical examination and tunning forks tests assessment, as well as, complete audiological tests, within 1-year following-up period. Results: Mean age in children (5.5±3.41 SD) and in adolescents and adults (25.5±1,78 SD) and (53%) males and (47%) females. Main usual reason of pure conductive hearing loss, among children was otitis media with effusion in about (55.55%), with association to adenoid hypertrophy (89.76%), while in adolescents and adults was otosclerosis (35%). Most common otoscopic findings was tympanic membrane retraction (44.73%) and the commonest chief complain was earache (68.42%). Conclusions: Most common cause of pure conductive hearing loss, in children was otitis media with effusion, with high associations between it and adenoid hypertrophy, while in adolescents and adults, it was otosclerosis.